Associations between sleep consolidation in infancy and peer relationships in middle childhood. Issue 2 (21st November 2017) - Larose‐Grégoire, Élodie; Bernier, Annie; Dirks, Melanie; Perrier, Rachel
Abstract: Sleep plays an important role in many aspects of children's development. Research on children's sleep and their peer relationships has begun to emerge in the last years. However, these studies are mostly cross‐sectional. The current study aimed to investigate the associations between infant sleep and peer relationships in middle childhood. The sample comprised 72 children. Sleep was measured at 1 year using a sleep diary completed by mothers. In the second and third grades of elementary school (7 and 8 years of age), mothers and fathers reported on their children's functioning with peers. When they were in third grade, children were interviewed regarding their friendship quality with a best friend. Results revealed negative associations between children's sleep consolidation (i.e., ratio of nighttime sleep) and parent‐reported peer problems, and positive associations between sleep consolidation and perceived friendship quality. These findings suggest that well‐regulated sleep in infancy may help children develop the skills necessary for later appropriate social functioning in peer contexts.